The Effect Of Suggested Exercises Using Rubber Bands In The Rehabilitation Of Patients With Partial Rupture Of The Hamstring Muscle - Ahmed , EmadKadhom (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research came in the development of exercises to rehabilitate the rupture of the sympathetic muscle using rubber bands, which would rehabilitate the athlete from the injury that hinders him from performing his duties in his specialized sport because of these means of ease in performance and the desire that they do not lead to pain And to the dangers of use as a result of excessive use because they have light and controlled weights and in bright colors that motivate practice by the injured athlete, as well as they are new, modern tools that always arouse the desire of the injured athlete to use them, which makes him feel help to restore his position as soon as possible, and the study aimed to prepare suggested exercises using the tapes Rubber bands in rehabilitating people with partial rupture of the hamstring muscle, and identifying the effect of exercises suggested using rubber bands in rehabilitating those with partial rupture of the hamstring muscle. (100%) of the research community, a clinical diagnostic examination of the injury was carried out by a specialized doctor, and a radiological examination of the research sample was carried out under the supervision of a medical team specialized in the twin muscle from the specialized staff at Baquba Teaching Hospital after clarifying the idea of research and selecting the sample, and after: The presence of a partial rupture of one of the twin muscles was found to the members of the research sample, and field research procedures included conducting experiments and The tests, which included (pain degree, force sensor, kinetic range), the rehabilitation program, first unit, started on Thursday, 17/1/2019 at three in the afternoon, and the exercises ended on Tuesday, 26/2/2019, and the total of them was (18) units and time (35-40) minutes for each qualifying unit, and the researcher concluded The rehabilitative exercises using rubber bands have a positive effect in the rehabilitation of partial rupture of the hamstring muscle for athletes through the evolution of the research variables , and the researcher recommends adopting the method set in the rehabilitation of the hamstring muscle because of the results shown by the development of the research sample.